Call me Mrs. Miracle [large type] - Macomber, Debbie (Thorndike Press large print basic, 2010)
While working in the toy department of a family-run department store in New York City, Emily Merkle aka. Mrs. Miracle, seizes the opportunity to connect Holly, who is searching for the perfect robot for her nephew, with Jake, the store owner's son.